ANALYSIS OF COMPLIANCE LEVEL TOWARDS SMK3 AMONG CONSTRUCTION PROJECT WORKERS - Ratna Sopiyatul Imamah; Dimas Aji Purnomo; Sunarko (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The construction industry is experiencing increasing complexity that has an impact on occupational safety risks. Dynamic work environments trigger workers' non-compliance with established safety procedures. Many construction projects experience work accidents due to weak SMK3 implementation systems in the field. Workers often ignore safety instructions due to lack of motivation, weak organizational culture, and low risk understanding. This study aims to analyze the factors that influence compliance with SMK3 among construction project workers. This study uses a qualitative approach based on literature review through a systematic analysis of academic sources published in 2023–2025. This study reveals that organizational culture, intrinsic motivation, risk understanding, and technology utilization have a major contribution to worker compliance. Systems that involve workers in formulating safety policies show higher levels of compliance. Application-based surveillance technology helps improve worker reporting and awareness in the field. Risk-based training that is developed in an applicative manner has proven to be more effective than formal training. This study concludes that compliance with SMK3 is formed through synergy between managerial systems and individual behavior. Companies need to build a safety culture that is applied consistently across all project lines. Project management needs to provide simulation-based training and real-time reporting systems to increase risk awareness. Researchers recommend an integrative strategy involving two-way communication, safety incentives, and the use of adaptive technology to establish sustainable compliance. A safety system that is adapted to field realities will increase the effectiveness of SMK3 implementation in the construction sector.